L’atelier « H » ou la représentation de l’adaptation dans l’élaboration du plan climat de Paris - Guillaume Simonet (VertigO, 2011)
Adaptation to climate change is attracting more and more attention, as much in scientific fields as in political spheres. However, its implementation remains fragmented, especially in the urban areas of industrialised countries despite their significant vulnerability to climate hazards due to high density of populations and economic activities. The City of Paris’ Climate Plan was developed in 2006 through a participatory approach and includes a chapter dedicated to adaptation, based on the final report from the workshop concerning adaptation in Paris (named Workshop H). This paper reports the retrospective study conducted with the organizers (municipal and consultants) of the Climate Plan, observers and participants involved in Workshop H. Results suggest it is difficult to achieve a clear collective understanding of what adaptation to climate change implies and what it looks like once it is translated into actions in an urban area such as Paris. Among the main barriers towards a collective understanding, is the recent awareness of climate change, the semantic ambiguity behind the word “adaptation” as well as the overlap between mitigation and adaptation concepts.